Evaluation of anthropometrical reference parameters for hemoglobin mass in endurance athletes - Schumacher, Y. O.; Ahlgrim, C.; Pottgiesser, T. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: Blood volume and hemoglobin mass (tHb) are new emerging parameters in exercise physiology. The appropriate anthropometrical reference for these variables has not yet been investigated. In most current investigations, body weight is used in this context. The aim of the present study was therefore to evaluate three different anthropometrical parameters (body weight, body surface area [BSA] and lean body mass [LBM] with respect to tHb. Methods: Sixty-five healthy male endurance athletes underwent a tHb determination (optimised CO rebreathing method) and anthropometrical evaluation (skinfold measurement) with estimation of body weight, LBM and BSA. Correlation analysis was performed; the correlations of the different anthropometrical reference ratios were compared and evaluated with regards to body composition. Results: LBM showed the best correlation with tHb (R=0.81), although no significant differences between the three anthropometrical references were found (BSA R=0.76, body weight R=0.77). In contrast to tHb/body weight, tHb/LBM was independent of body fat content and thus body composition. Conclusion: The current study demonstrated no statistical difference between various anthropometrical references for tHb, which might be due to the anthropometrically homogenous study group of lean, endurance trained athletes. However, the significance dependence of body weight on body fat content indicates that this might not be the case in athletes of other somatotypes. It is therefore suggested that LBM instead of body weight should be used as anthropometrical reference when investigating tHb in athletes.